(untitled) (Swiss Medical Weekly, 2017)
This review aims to assist emergency physicians in finding the underlying aetiology when a patient presents with dizziness to the emergency department. After reading this review, the emergency physician will be able to consider the most relevant differential diagnoses and have an idea about dangerous aetiologies that require immediate action. The emergency physician will also know what diagnostic steps need to be taken at what time, such as the three-component HINTS Test (Head Impulse, Nystagmus, and Test-of-Skew), which helps with distinguishing central from peripheral causes of the acute vestibular syndrome. Furthermore, episodic vestibular syndromes and chronic vestibular syndromes are discussed in detail. The five most frequent categories of dizziness are vasovagal syncope / orthostatic hypotension (22.3%), vestibular causes (19.9%), fluid and electrolyte disorders (17.5%), circulatory/ pulmonary causes (14.8%) and central vascular causes (6.4%). Given that it would neither be economical nor practical to send all patients to specialists from the start, we present general guidelines for the diagnostic workup of patients presenting with dizziness to the emergency department. This review will focus on epidemiology, aetiologies, differential diagnoses and diagnostics. Treatment is described in a separate article.